PENGARUH PENDIDIKAN, PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA BANK BTN KC MAKASSAR - Muhammad Imam Dzakwan Satria S; Muh. Nur Rasyid; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of education, training, and career development on employee performance at PT Bank Tabungan Negara (Persero) Tbk. Makassar Branch Office. This research used a quantitative approach involving 98 permanent (organic) employees as respondents. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, and the coefficient of determination (R²). The results show that the education variable has a positive but insignificant effect on employee performance, with a regression coefficient of 0.100 and a significance value of 0.468 > 0.05. The training variable has a positive and significant effect on employee performance, with a regression coefficient of 0.267 and a significance value of 0.001 < 0.05. Career development also has a positive and significant effect on employee performance, with a regression coefficient of 0.366 and a significance value of 0.000 < 0.05, and is the most dominant variable. The coefficient of determination (R²) value of 0.378 indicates that education, training, and career development explain 37.8% of the variation in employee performance, while the remaining percentage is influenced by other factors outside the research model. The reliability test results indicate that all variables have Cronbach’s Alpha values above 0.60, meaning that the research instruments are reliable.